PENGARUH PEMAHAMAN HUKUM BISNIS TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - darma purba, dianisa sinaga; Ritonga, Nazla; Ambarwati, Ririn; Hasyim (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research aims to determine the relationship between understanding business law and interest in entrepreneurship among students and to find out how business law education helps students manage risks and face business challenges, with a focus on the situation at the economics faculty at Medan State University. This research uses a qualitative approach which aims to understand conditions in depth in the natural context of what happens in the study field. The data collection technique used is primary data through questionnaires distributed to students. This questionnaire measures respondents' attitudes, opinions, hopes and desires regarding understanding of business law and interest in entrepreneurship. The research results show that students who take business law courses consistently attend lectures and understand the basic concepts of business law. Respondents considered that understanding business law is very important for an entrepreneur, which helps them feel more confident in starting a business because it can reduce the risks of entrepreneurship. The majority of respondents agreed that understanding business law is a very important aspect for an entrepreneur. These results indicate that business law education not only improves students' legal understanding but also influences their interest and readiness for entrepreneurship.